Two rare variants reveal the significance of Grainyhead‐like 3 Arginine 391 underlying non‐syndromic cleft palate only. (19th April 2022) - Huang, Wenbin; He, Qing; Li, Mingzhao; Ding, Yi; Liang, Wei; Li, Weiran; Lin, Jiuxiang; Zhao, Huaxiang; Chen, Feng
Abstract: Objectives: Non‐syndromic cleft palate only (NSCPO) is one of the most common craniofacial birth defects with largely undetermined genetic etiology. It has been established that Grainyhead‐like 3 (GRHL3) plays an essential role in the pathogenesis of NSCPO. This study aimed to identify and verify the first‐reported GRHL3 variant underlying NSCPO among the Chinese cohort. Methods: We performed whole‐exome sequencing (WES) on a Chinese NSCPO patient and identified a rare variant of GRHL3 (p.Arg391His). A validated deleterious variant p.Arg391Cys was introduced as a positive control. Zebrafish embryos injection, reporter assays, live‐cell imaging, and RNA sequencing were conducted to test the pathogenicity of the variants. Results: Zebrafish embryos microinjection demonstrated that overexpression of the variants could disrupt the normal development of zebrafish embryos. Reporter assays showed that Arg391His disturbed transcriptional activity of GRHL3 and exerted a dominant‐negative effect. Interestingly, Arg391His and Arg391Cys displayed distinct nuclear localization patterns from that of wild‐type GRHL3 in live‐cell imaging. Bulk RNA sequencing suggested that the two variants changed the pattern of gene expression. Conclusions: In aggregate, this study identified and characterized a rare GRHL3 variant in NSCPO, revealing the critical role of Arginine 391 in GRHL3. Our findings will help facilitate understanding and genetic counseling of NSCPO.